Prevalences and trends of human oral protozoan parasites - ADAMU, VE; Amaechi, Augustine A.; Ajaero, C. M. U.; Eneojo, NIF; Nwoke, Bright Ekejiuba Bertrand; Ukaga, Chinyere N. (Orapuh Journal, 2020)
Protozoan parasites are microscopic, unicellular organisms, of a group of phyla of the kingdom Protista, that can be free-living or parasitic. These organisms can live, and reproduce their kind, in human tissues. This accounts, in part, for why just a single protozoan can survive and infect humans so profoundly. A lot of people suffer severe morbidity connected to parasites. Parasitic protozoan parasite infections are associated with a lack of sanitation and access to safe and potable water. These infections make it impossible for poor populations to enjoy the full potentials of a healthy body and vitality and this hampers their productivity and, consequently, their social life and economic progress. Protozoan parasites that adapt to and live in the oral environment are called, ‘oral protozoan parasites’. The appreciation of the fact that human oral protozoan parasites exist has long been documented by the empirical works of several researchers and scholars. Many of these works also indicated that Entamoeba gingivalis and Trichomonas tenax, which are parasitic oral protozoan parasites, are found only in the oral cavity. It is well known that the presence of these oral protozoan parasites may be established both in persons with pathological alterations in the oral cavity and those with no such symptoms. Human oral protozoan parasites cause gingival itch, palatal sore, halitosis, fatigue, fever, headaches, and periodontal tissue damage. Researchers have reported that the presence and impact of oral protozoan parasites may vary with age, gender, oral hygiene measures, general and oral health status, immune status, and alcohol and tobacco usage. Oral protozoan parasites constitute a growing concern to health authorities and researchers because they can either compromise oral integrity and health or complicate clinical intervention goals. The intentional control of oral parasites remains the only valid clinical option to improve the quality of life for sufferers and, by extension, all humans.